PENANGKAPAN IKAN SECARA ILLEGAL DI PERAIRAN INDONESIA - Moh Tamsil Tamrin (Fakultas Hukum Universitas Muhammadiyah Palu, 2020)
The Unitary State of the Republic of Indonesia (NKRI), known as the Archipelagic State (Archipelagic State), because it is an archipelago perched along the equator, has a sea area of 5.8 million km² consisting of a territorial sea with an area of 0.8 million km2, the archipelago sea 2.3 million km2 and Exclusive economic zone 2.7 million km2. In addition, Indonesia has 17,480 islands and a coastline of 95,181 km2 which have a potential source of marine biological wealth stored in it. Not handling the problem of illegal fishing professionally by the government makes the problem complex and complicated so this condition is exploited by fishermen from other countries to carry out activities that violate the provisions of the legislation, for example the Philippines is known as the largest tuna exporting country in the world, but 70 percent of the tuna they export comes from Indonesian waters.Keyword: Illegal. Fish catching